2011
DOI: 10.1200/jco.2011.35.4498
|View full text |Cite
|
Sign up to set email alerts
|

Development and Independent Validation of a Prognostic Assay for Stage II Colon Cancer Using Formalin-Fixed Paraffin-Embedded Tissue

Abstract: This gene signature represents a novel prognostic biomarker for patients with stage II colon cancer that can be applied to FFPE tumor samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(152 citation statements)
references
References 27 publications
2
150
0
Order By: Relevance
“…Amplified products were hybridized to the Almac Colorectal Cancer DSA microarray platform (Almac, Craigavon, United Kingdom; ref. 40). Following quality control, TOP1 mRNA expression data were available for a total of 688 unique samples, including 580 from patients with stage III disease.…”
Section: Top1 Mrna Expressionmentioning
confidence: 99%
“…Amplified products were hybridized to the Almac Colorectal Cancer DSA microarray platform (Almac, Craigavon, United Kingdom; ref. 40). Following quality control, TOP1 mRNA expression data were available for a total of 688 unique samples, including 580 from patients with stage III disease.…”
Section: Top1 Mrna Expressionmentioning
confidence: 99%
“…After isothermal amplification, 50 or 100 ng of total RNA was amplified to 4 to 7 mg of biotinylated cDNA complementary to the original mRNA. The amplification step has been optimized for RNA extracted from FFPE specimens 15,16 and has shown comparable differential expression profiles to corresponding fresh-frozen tissues. 17 After amplification, we hybridized 3.75 mg of amplified cDNA to the GeneChip Human Gene 1.0 ST Array (Affymetrix).…”
Section: Messenger Rna Expression Profiling Arraymentioning
confidence: 99%
“…On the basis of a different prognostic assay, Kennedy and colleagues (29) reported that the 634-probes signature used in the ColDx test (Almac Diagnostics) also had the ability to discriminate risk of recurrence in patients with stage II colon cancer (HR ¼ 2.53; P ¼ 0.003). However, these findings did not account for the MMR characterization, and the sample size of the validation set was limited and enriched for recurrence (29). The relative merit of enhanced nodal characterization versus genomic profiling of the primary tumor is a critical question for future study.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, gene signatures have been developed from FFPE tumor samples to identify patients with stage II colon cancer who are at higher risk of disease recurrence (28)(29)(30)(31)(32). The study by Gray and colleagues (28) was designed as a validation study based on prospectively specified retrospective analyses of the QUASAR (QUick And Simple And Reliable) trial.…”
Section: Discussionmentioning
confidence: 99%